Analyzing the effectivity of evidence-based practice in health science higher education: a narrative review - Victória Guzzo da Silva; Dafne Port Nascimento; Sarah Beatriz Obadovski Alves Nascimento; Amanda Costa Araujo (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Although multiple strategies have been suggested for evidence-based practice educational interventions, few studies have focused on the development of abilities for evidence-based practice implementation. OBJECTIVE: To explore the effectiveness of evidence-based practice in higher education and understand its teaching methods. DESIGN AND SETTING: Narrative review was conducted at the Universidade Municipal de São Caetano do Sul, Brazil. METHODS: Narrative review included research studies that measured any type of evidence-based practice teaching method and its effectiveness. Searches included publications from inception to June 2022, conducted on MEDLINE, EMBASE, CINAHL, CENTRAL, ERIC, and the Cochrane Library. Two independent authors descriptively extracted and analyzed the data. The methodological quality of the studies was also analyzed. RESULTS: The results determined that 79.2% of the studies proved their effectiveness. Teaching methods varied according to the time period, format, and types of questionnaire. CONCLUSIONS: Most studies demonstrated the effectiveness of the chosen teaching methods. This study shows the importance of health professionals using evidence-based practice to ensure effective patient treatment.